Immunogenicity of SARS-CoV-2 mRNA intramuscular vaccination in patients with muscular disorders - Kasai, Ryousuke; Funato, Michinori; Maruta, Kanako; Yasuda, Kunihiko; Minatsu, Hiroshi; Ito, Junji; Takahashi, Kazuhiro (Frontiers in Immunology, 2023)
Backgrounds: Little clinical data is available on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in patients with muscular disorders (MDs). The immunogenicity of SARS-CoV-2 vaccines against MDs, in particular, remains unknown. Thus, this study aimed to confirm the immunogenicity and safety of the SARS-CoV-2 vaccine against MDs. Methods: All participants were vaccinated with two doses of mRNA vaccines (BNT162b2, Pfizer-BioNTech). The serum samples were collected from each patient on the day of second dose of vaccination, and then, consecutively, after one month, three months, and six months. Anti-SARS-CoV-2 IgG levels were determined using the Abbott SARS-CoV-2 IgG II Quant assay. Results: We evaluated 75 individuals, including 42 patients with MDs and 33 patients with non-muscular disorders (non-MDs). Non-MD patients primarily include those with severe motor and intellectual disabilities. The median age of the patients was 32 years (range 12–64 years). After one and three months following the second immunization, patients with MDs had lower antibody responses. Furthermore, three months following the second immunization, the proportion of high responders among patients with MDs decreased significantly compared to that among patients without MDs (p-value of less than 0.01). No serious adverse events were observed in patients with or without MDs. Conclusion: Intensity and latency of antibody response were suppressed in patients with MDs. Although MDs may be a key contributor in predicting the antibody response to SARS-CoV-2 vaccination, SARS-CoV-2 immunization in MDs needs extensive research.